Electrical Muscle Stimulation Normalizes Blood Glucose Level in Streptozotocin-induced Diabetic Rats - Lu, W.-Z.; Ni, Y.; Meng, X.-Y. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2013)
Patients with diabetes suffer from slow-to-heal wounds, which often necessitate amputation. Electrical stimulation has been shown to reduce the healing time in such patients.This study aimed to determine the effect of electrical muscle stimulation on insulin resistance, glucose absorption, and blood lipids in type 2 diabetic rat model.Diabetic rats and normal rats were treated with electrical muscle stimulation (10 Hz, 2 mA, 20 ms) for 40 days. Blood glucose, lipids, insulin and resistin were measured to evaluate antidiabetic activity of electrical stimulation.Diabetic rats treated with electrical muscle stimulation resulted in a significant decrease in the concentration of plasma total cholesterol and triglycerides, improved the body weight. Furthermore, electrical stimulation markedly decreased blood glucose level in the diabetic rats. The levels of plasma insulin and resistin exhibited significantly lower in the diabetic rats treated with electrical stimulation than those of the model group. Extending the stimulation up to 20 min from 10 min did not cause significant changes in all the measured blood biochemistry indices and body weight.This study showed that electrical muscle stimulation can improve adipose metabolic disturbance in the experimental type 2 diabetic rats, can effectively ameliorate insulin resistance and plasma glucose transport by decreasing the levels of plasma resistin.
Keywords: electrical stimulation; glucose; insulin; resistin